Advanced cancer patient preferences for receiving molecular profiling results. Issue 10 (11th August 2020) - Best, Megan; Butow, Phyllis; Jacobs, Chris; Juraskova, Ilona; Savard, Jacqueline; Meiser, Bettina; Goldstein, David; Ballinger, Mandy; Bartley, Nicci; Napier, Christine; Davies, Grace; Thomas, David; et al.
Abstract: Objective: This study aimed to discern preferences for receiving somatic molecular profiling (MP) results in cancer patients who have given consent to undergo testing. Methods: We conducted a mixed‐methods study to explore patients' views on which MP results they would like to receive and why. Advanced cancer patients (n = 1299) completed questionnaires after giving consent to participate in a parent genomics study and undergoing MP. A subset of patients (n = 20) participated in qualitative interviews. Results: Almost all (96%) participants were interested in receiving results which would direct cancer treatment (ie, were actionable). A smaller majority wanted to access results which were not actionable (64%) or were variants of unknown significance (60%). Most (86%) were interested in finding out about germline findings, though not as a priority. Themes identified in interview data were: (a) Cancer is the focus; (b) Trust in clinicians; and (c) Respect for a right not to know. Conclusions: The majority of advanced cancer patients undergoing MP prioritised results which would lead to treatment options. They trusted their oncologists to help them navigate the results return process. While there was interest in knowing about other results, this was a lesser priority. Nevertheless, given high levels of interest in receiving all results, ethical aspects of not providing uninformative results requires further research, including a consideration of patient rationales for desiring this information and what health professionals can and should do to support patients in the absence of meaningful information being available.